Application Research Progress of Continuous Blood Glucose Monitoring System in Patients with Gestational Diabetes Mellitus - Yuan GAO, Min ZHOU (Zhongguo quanke yixue, 2022)
The "Decision of the Central Committee of the Communist Party of China and the State Council on Optimizing the Fertility Policy to Promote the Long-term Balanced Development of the Population" issued in June 2021made a major decision to implement the three-child policy, and the number of pregnant women will increase significantly. As one of the common complications during pregnancy, gestational diabetes seriously affects the health of pregnant women and fetuses. Continuous blood glucose monitoring has been called "the road map for effective self-management" and is critical in the management of blood glucose in people with gestational diabetes. This article reviews the development of continuous blood glucose monitoring and its application and impact in patients with gestational diabetes, in order to promote the clinical application of continuous blood glucose monitoring, encourage patients with gestational diabetes to participate in diabetes response and improve accurate blood glucose management.